Proses Produksi Mobil Taksi Baru dan Mobil Taksi Bekas Menjadi Kendaraan Pribadi: Production Process of New and Used Taxi Cars to Become Personal Vehicles - Rizki Andhika; Tjokorda Gde Tirta Nindhia (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
Taxis are one of the modes of public transportation that are often found in big cities. This study will discuss the production process of new taxis and used taxis until they become cars that are ready to be used as private vehicles by the general public. New taxis will be produced according to taxi standards set by the relevant company. Meanwhile, used taxis are cars that have been operating for 5 years as taxis, then restored to become private vehicles. The production process of new taxis includes various steps from planning to quality control, which aims to ensure that the taxis produced have high quality and a luxurious appearance. Meanwhile, the production process of used taxis requires detailed and thorough checking and processes from the time the car arrives at the production site until production is completed. Through these two processes, in-depth insights are obtained on how to maintain the performance and quality of cars, both new and used, so that they are always optimal.